Internal Gene Cassette From a Human-Origin H7N9 Influenza Virus Promotes the Pathogenicity of H9N2 Avian Influenza Virus in Mice - Zhang, Miaomiao; Zhao, Chen; Chen, Hongjun; Teng, Qiaoyang; Jiang, Lang; Feng, Daobin; Li, Xuesong; Yuan, Songhua; Xu, Jianqing; Zhang, Xiaoyan; Li, Zejun (Frontiers in Microbiology, 2020)
H9N2 avian influenza virus (AIV) is one of the most widely circulating viruses in poultry, and poses a huge potential threat to human health due to its frequent gene reassortment with other influenza virus. In this study, we generated a series of H9N2-H7N9 reassortant viruses and examined their pathogenicity in mouse model.We found that, HA or combined HA and NA replacement on the H9N2 background, led to no substantial change in the virus-induced pathogenicity, whereas H9N2 virus containing H7N9 internal genes conferred significant higher virulence in comparison to the parental H9N2 virus. This increased pathogenicity is associated with enhanced viral replication both in mice and in MDCK cells. We further demonstrated that the viral ribonucleoprotein complex from H7N9 virus possessed higher activity than that from its H9N2 counterpart. Collectively, our data demonstrated genetic compatibility between H9N2 and H7N9 virus facilitated the re-assortment between H7N9 and H9N2 viruses co-circulated in poultry, and internal genes replacement would convert H9N2 virus into a novel threat to human health.